1986
DOI: 10.1111/j.1740-8261.1986.tb00022.x
|View full text |Cite
|
Sign up to set email alerts
|

Two‐year Non‐recurrence Rates for Equine Ocular and Periorbital Squamous Cell Carcinoma Following Radiotherapy

Abstract: Seventeen horses with a total of 18 ocular or periorbital squamous cell carcinomas were irradiated with Strontium-90 surface therapy, or Radon-222, Iodine-125, or Iridium-192 interstitial implants. Tumors were surgically cytoreduced prior to irradiation in all but two horses. Follow-up datawas obtained for 2 years in each horse. Two-year non-recurrence rates (no grossly visible evidence of tumor) were 87.5% for wSr beta therapy, and 60% (70% when corrected for non-tumor-related deaths) for interstitial implant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 6 publications
1
55
0
Order By: Relevance
“…7,8,21,23 King et al 7 reported a 25% recurrence rate for ocular SCC in horses after treatment with radiation therapy using beta (Sr 90 ) and gamma (Ir 192 ) radiation, and Walker et al 8 reported recurrence rates for ocular and periorbital SCC in horses after treatment with radiation therapy of 17.5% for Sr 90 and 20% for interstitial (Rn 222 , I 125 , and Ir 192 ) radiation. A recurrence rate of 11.9% for ocular and adnexal SCCs after treatment with adjuvant radiation therapy across all anatomic locations is comparable to that reported in other studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8,21,23 King et al 7 reported a 25% recurrence rate for ocular SCC in horses after treatment with radiation therapy using beta (Sr 90 ) and gamma (Ir 192 ) radiation, and Walker et al 8 reported recurrence rates for ocular and periorbital SCC in horses after treatment with radiation therapy of 17.5% for Sr 90 and 20% for interstitial (Rn 222 , I 125 , and Ir 192 ) radiation. A recurrence rate of 11.9% for ocular and adnexal SCCs after treatment with adjuvant radiation therapy across all anatomic locations is comparable to that reported in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Strontium 90 is only indicated for superficial tumors that are or have been debulked to a tumor depth ≤ 3 mm because 80% of the radiation dose is absorbed in the first 2 mm of tumor. 8,27 Overall, the risk associated with radiation therapy using Sr 90 is low, making its use for a neoplastic disease process justifiable. Because of the delivery mechanism, this treatment is most often used for eyelid and periocular tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Adjunctive treatment may involve cryotherapy (Schoster 1992;Bosh and Klein 2005), radiofrequency hyperthermia (Wilkie and Burt 1990), photodynamic therapy (English et al 1990;Guiliano et al 2008;Michau et al 2012), immunotherapy (McCalla et al 1992), chemotherapy with cisplatin (Theon et al 1993), 5-fluorouracyl (Pucket and Gilmour 2014) or mitomycin C (Clode et al 2012), radiotherapy such as brachytherapy (King et al 1991), interstitial therapy (Chachory et al 2002), and beta radiation (Walker et al 1986;Rebhun 1990;Plummer et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The radiation is delivered at between 0.3 and 0.5 Gy/h while the implant is in place, with prescribed total doses ranging between 50 and 90 Gy depending on the size, location and type of tumour to be treated and reported success rates of between 74 and 100% (Walker et al . , ; Theon and Pascoe ; Theon ; Knottenbelt and Kelly ; Byam‐Cook et al . ).…”
Section: What Are the Different Forms Of Radiotherapy?mentioning
confidence: 99%